High prevalence of Trypanosoma cruzi infection in shelter dogs from southern Louisiana, USA - Ardem Elmayan; Weihong Tu; Brandy Duhon; Preston A. Marx; Wendy Wolfson; Gary Balsamo; Claudia Herrera; Eric Dumonteil (2019)
Chagas disease is a zoonotic disease caused by the protozoan parasite Trypanosoma cruzi. The role of dogs as sentinels has been proposed in multiple regions, as they are a domestic reservoir for T. cruzi. Our objective was to determine the prevalence of T. cruzi infection in shelter dogs from southern Louisiana, and assess its magnitude and distribution.A total of 540 dogs were enrolled, from 20 animal shelters, and tested for T. cruzi infection by serological tests (rapid test, ELISA and western blot) and PCR. We documented a high prevalence of T. cruzi infection with at least 6.9% (95% CI: 5.0-9.3%) seropositive and 15.7% (95% CI: 12.9-19.1%) PCR-positive dogs. Serological tests showed limited agreement, and concordance between serology and PCR was higher when considering reactivity to single serological tests. Trypanosoma cruzi infection was distributed evenly among shelters. Infection was significantly correlated with age (R2 = 0.99), indicating an incidence of new cases of 2.27 ± 0.25% per year.Trypanosoma cruzi infection is a significant and widespread veterinary problem in shelter dogs in the region, although it is mostly unnoticed by health professionals. This highlights the need for greater awareness of T. cruzi infection among the veterinary community and dog owners.